1977
DOI: 10.1136/jcp.30.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-antitrypsin bodies in the liver.

Abstract: SUMMARY The cytoplasmic bodies in hepatocytes thought to indicate possession of the Z allele for a1-antitrypsin deficiency were found at necropsy in 10 of 64 adults with cirrhosis, four of nine with hepatic fibrosis, and four of 15 with hepatocellular carcinoma. They were also found in six of 76 adults with severe panacinar emphysema, and in four of a control series of 110 adults with neither emphysema nor liver disease. The association of the bodies with each of the three liver diseases was statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0
2

Year Published

1978
1978
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 24 publications
3
18
0
2
Order By: Relevance
“…The results are shown in the Table, which also gives the results in a previous control series (Blenkinsopp and Haffenden, 1977). Chi-square tests revealed no significant difference between any test group and the controls, and thus no evidence of an association between al-antitrypsin deficiency and peptic ulceration.…”
Section: Results and Commentmentioning
confidence: 57%
See 1 more Smart Citation
“…The results are shown in the Table, which also gives the results in a previous control series (Blenkinsopp and Haffenden, 1977). Chi-square tests revealed no significant difference between any test group and the controls, and thus no evidence of an association between al-antitrypsin deficiency and peptic ulceration.…”
Section: Results and Commentmentioning
confidence: 57%
“…Probably all persons with a PiZ allele have typical periodic acid-Schiff positive, diastase resistant, rounded bodies in the cytoplasm of their hepatocytes (Blenkinsopp and Haffenden, 1977), and these bodies rarely occur in persons with normal PiMM phenotype (Bradfield and Blenkinsopp, 1977). Andre et al (1974) reported that 10.5% of 114 patients with chronic duodenal ulcer, and 9-6 % of 83 with chronic gastric ulcer, had levels of al-antitrypsin in the heterozygous (PiMZ) range, compared with 3-3% of 118 controls.…”
mentioning
confidence: 99%
“…Immunocytochemicat and histological studies using intracytoplasmic liver AAT globules as markers have suggested that there is an increased incidence of the Z allele in cases of HCC (Blenkinsopp and Haffenden 1977; or cirrhosis (Blenkinsopp and Haffenden 1977;Eriksson et al 1975), although phenotypic studies have shown no statistically significant increase of Z allele in cases of HCC and cirrhosis (Peters 1976;Theodoropoulos et al 1976). More recently, Kelly et al (1979), in a series of 42 cases of HCC and 98 controls, described typical AAT globules stained most strongly at the globule periphery in the non-neoplastic liver tissue of two (5%) of HCC.…”
Section: Discussionmentioning
confidence: 97%
“…In the Austrian study only 3 of the 9 homozy-seen in other hepatic cell types. [109][110][111][112][113] The liver biopsy may also be characterized by a variable degree of cholestasis, hegotes had clinically significant liver injury and only one had evidence of viral infection. 92 In a 14-year experience at St. patocellular necrosis, inflammatory cell infiltrate, bile duct epithelial cell destruction, and periportal fibrosis or cirrhosis.…”
Section: Aid Hepa 0043mentioning
confidence: 99%